A micelle nucleation model for the interaction of dodecyl sulphate with Lys49-phospholipases A(2) - Bortoleto-Bugs, Raquel Kely; Bugs, Milton Roque; Neto, Augusto Agostinho; Ward, R. J. (Elsevier B.V., 2007)
Bothropstoxin-I (BthTx-I) is a Lys49-PLA(2) from the venom of Bothrops jararacussu that lacks detectable catalytic activity, yet causes rapid Ca2+-independent membrane damage. With the aim of understanding the interaction between BthTx-I and amphiphilic molecules, we have studied the interaction of sodium dodecyl sulphate (SDS) with the protein. Circular dichroism and attenuated total reflection Fourier-transform infrared spectra of BthTx-I reveal changes in the alpha-helical organization of the protein at an SDS/BthTx-I molar ratio of 20-25. At SDS/BthTx-I ratios of 40-45 the alpha-helices return to a native-like conformation, although fluorescence emission anisotropy measurements of 2-amino-N-hexadecyl-benzamide (AHBA) demonstrate that the total SDS is below the critical micelle concentration when this transition occurs. These results may be interpreted as the result of SDS accumulation by the BthTx-I homodimer and the formation of a pre-micelle SDS/BthTx-I complex, which may subsequently be released from the protein surface as a free micelle. Similar changes in the alpha-helical organization of BthTx-I were observed in the presence of dipalmitoylphosphatidylcholine liposomes, suggesting that protein structure transitions coupled to organization changes of bound amphiphiles may play a role in the Ca2+-independent membrane damage by Lys49-PLA(2)s. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: bothropstoxin-I; Circular dichroism; fluorescence anisotropy; ATR-FTIR